2019
DOI: 10.1101/2019.12.20.885442
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PiVR: an affordable and versatile closed-loop platform to study unrestrained sensorimotor behavior

Abstract: Tools enabling closed-loop experiments are crucial to delineate causal relationships between the activity of genetically-labeled neurons and specific behaviors. We developed the Raspberry Pi Virtual Reality system (PiVR) to conduct closed-loop optogenetic stimulation of neural functions in unrestrained animals. PiVR is an experimental platform that operates at hightemporal resolution (>50 Hz) with low latencies (~10 ms), while being affordable (<$500) and easy to build (<6 hours). This tool was designed to be … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 70 publications
1
20
0
Order By: Relevance
“…These results reproduce the known effects of natural sugar or bitter (Flood et al, 2013; Thoma et al, 2016; Marella et al, 2006; Joseph and Heberlein, 2012; Das et al, 2014; Schwaerzel et al, 2003), providing reassurance that our activation paradigms are relevant to natural behavior. Our results also align with other studies that reported effects on locomotion or innate preference using optogenetic taste neuron activation (Aso et al, 2014; Tadres and Louis, 2020; Mohammad et al, 2017; Haberkern et al, 2019; DeAngelis et al, 2020; Stern and Yang, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…These results reproduce the known effects of natural sugar or bitter (Flood et al, 2013; Thoma et al, 2016; Marella et al, 2006; Joseph and Heberlein, 2012; Das et al, 2014; Schwaerzel et al, 2003), providing reassurance that our activation paradigms are relevant to natural behavior. Our results also align with other studies that reported effects on locomotion or innate preference using optogenetic taste neuron activation (Aso et al, 2014; Tadres and Louis, 2020; Mohammad et al, 2017; Haberkern et al, 2019; DeAngelis et al, 2020; Stern and Yang, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…(2020) present a portable flow‐through microscope to study planktonic communities that can be used in remote field locations. Tadres and Louis (2020) used the Raspberry Pi to create a low‐cost virtual reality platform (PiVR) that enables high‐resolution, optogenetic, closed‐loop experiments with small freely moving animals at up to 50 Hz. Kallmyer et al.…”
Section: Overview Of Applications Across the Biological Domainmentioning
confidence: 99%
“…Closed-loop systems are powerful tools to identify various strategies of an animal's sensorimotor transformation. They have been employed in many animal models including adult and larval Drosophila (Bahl et al, 2013;Tadres and Louis, 2019), larval zebrafish (Chen and Engert, 2014;Bahl and Engert, 2020), and C. elegans (Leifer et al, 2011;Kocabas et al, 2012).…”
Section: Discussionmentioning
confidence: 99%